ANALISA PENGARUH HUMAN RESOURCE MANAGEMENT TERHADAP FINANCIAL PERFORMANCE MELALUI VARIABEL INTERVENING LEARNING ORGANIZATION (Studi Kasus pada Kantor Akuntan Publik di Surabaya) - Hariyanto - (Business Accounting Review, 2016)
This study was conducted to know the influence of human resource management to financial performance through learning organization as an intervening variable in case study on Public Accountant Firms in Surabaya. Financial performance became one of the most important variable that could measure the performance of public accountant firms. Another variables such as Human resource management played a role in creating the financial performance in the public accountant firms. On the other hand, human resource management application could not be separated from the support of learning organization that was in the public accountant firms.The data analysis technique used in this study was partial least squares to describe the relationship between variables. The results showed that human resource management and learning organization positively and significanthy affected the financial performance public accountant firms in Surabaya.